PENGARUH KUALITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, PEMAHAMAN STANDAR AKUNTANSI PEMERINTAH DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN KABUPATEN SELUMA - Puspita, Diana; Fadli, Fadli; Halimatusyadiah, Halimatusyadiah (JURNAL FAIRNESS, 2020)
This study aimed to examine the effect of Human Resource Competence, Utilization of Information Technology, Understanding of Government Accounting Standards and Internal Control Systems on the Quality of Regional Financial Reports. This research is a type of research with a quantitative approach to survey methods. The sample in this study was 29 Regional Apparatus of Seluma Regency. Sampling of respondents in this study is based on the census method. The respondents from each Regional Apparatus are financial administration officials, treasurers, and financial administration staff at agencies, offices, offices, sub-districts, and regional secretaries. The results showed that Human Resource Competence, Utilization of Information Technology, Understanding of Government Accounting Standards and Internal Control Systems on the Quality of Regional Financial Reports. Keyword: Human Resource Competence, Utilization of Information Technology, Understanding of Government Accounting Standards and Internal Control Systems, Quality of Regional Financial Reports.